Pola Jaringan Komunikasi Layanan Kesehatan bagi Penyandang Disabilitas Korban Erupsi Gunungapi Merapi - Wuri Rahmawati; Hari Akbar Sugiantoro (Universitas Ahmad Dahlan, 2019)
The objective of this research in the future is to get a disaster communication design especially for disability communities. And the short objective of this research are to know the health service communication network design especially for disability communities.This research used a qualitative method with purposive sampling. Informant of this research are disability,government, NGO and volunteer. Primary and secondary data used in this research. Interview, forum group discussion and observation are to get primary data and than writing and documentation are to get secondary data.The results of this research showed that the disability communities as victims of the Merapi volcanic eruption in 2010 had not received special treatment either during evacuation or while in refugee camps. The facilities for evacuation and evacuation facilities are not yet diffable-friendly. While health services were available for victims of the Merapi volcanic eruption. Volunteers deliver or announce information about the availability of health services to refugees using loudspeakers (microfon) so that they can be heard simultaneously by refugees including persons with disabilities except deaf.Pattern of communication network for health services for victims of Merapi volcanic eruptions, namely the wheel pattern, volunteers as sources or information centers regarding the availability of health services for disaster victims (refugees). Whereas the role formed in the health service communication network for disabilities communities is volunteers as Liaison (person who outside the group that connect disabilities groups with medical team groups), medical teams as opinion leaders (people who are asked for opinions on health and influence disabilities to behave accordingly with recommendations in the treatment and prevention of diseases and persons with disabilities (deaf) as isolates (person that have very limited or minimal to access health services information as a result of their limitations and methods of delivering information using loudspeakers. Â